Hounsfield unit-to-hematocrit ratio as a quantitative marker for cerebral venous sinus thrombosis: A retrospective diagnostic study - Amran, Muhammad Yunus; Hidayah, M; Akbar, Muhammad; Bintang, Andi; Hawari, Irbab (Acta Biomedica Atenei Parmensis, 2025)
Background and Aim: Cerebral Venous Sinus Thrombosis (CVST) is a rare but potentially life-threatening condition that requires advanced imaging modalities, such as magnetic resonance venography (MRV) or computed tomography venography (CTV), for diagnosis. However, access to these diagnostic tools is often limited in resource-constrained settings. There is an unmet need for simpler, cost-effective, and rapid diagnostic methods to facilitate early detection of CVST. This study aims to evaluate the utility of the Hounsfield unit (HU)/ hematocrit (Hct) ratio derived from non-contrast CT imaging as a novel diagnostic marker for CVST and explore its correlation with hematological parameters, while identifying common symptoms and demographic patterns. Methods: This cross-sectional study was conducted between September and October 2024. Data were collected retrospectively from patients diagnosed with CVST between January 2022 and August 2024 at a tertiary care center. The study variables included Hct, platelet count (Plt), HU values from CT scans, and the HU/Hct ratio. Data were analyzed and presented in summary tables, focusing on the relationship between imaging and hematological parameters. Results: A total of 93 patients with CVST were identified, with 74.2% being female and a mean age of 40 years. After applying inclusion criteria, 34 patients were analyzed. The study revealed a significant negative correlation between Hct and the HU/Hct ratio (p = 0.001). No significant correlation was observed between Plt and HU or the HU/Hct ratio. Common clinical presentations included headache (84%) and dizziness (35%), with CVST predominantly affecting women of reproductive age. Conclusion: The HU/Hct ratio demonstrates potential as an accessible and reliable diagnostic marker for CVST, particularly in resource-limited settings where advanced imaging is unavailable. This quantitative parameter could complement existing diagnostic workflows and aid in the early detection of CVST. Further validation through multicenter studies is recommended to establish its broader applicability. (www.actabiomedica.it)